Physiological Aspect of Agni W.S.R. to its Role in Metabolism - Preeti, Jaiswar; Yadav, Sarika; W J Chathurika, L A (International Research Journal of Ayurveda & Yoga, 2025)
Introduction: Agni in Ayurveda is a deeply significant concept, often referred to as digestive fire, or biological fire, and it plays a central role in the body’s overall health, wellness, and balance. It is a key component of our body’s digestion and metabolism. Agni is responsible for the digestion, absorption, and assimilation of food, which is necessary for life maintenance. Materials and Methods: The study methods include exploration of Agni-related literary review from classical Ayurvedic texts, research articles, and journals such as Google Scholar and Research Gate. Result: The coordinated function of Jatharagni, Bhutagni, and Dhatvagni ensures the proper transformation of food into energy and tissue elements. This study identifies Agni as the central regulatory force of digestion, metabolism, and overall physiological balance. Balanced Agni maintains systemic equilibrium and overall health, whereas its impairment leads to Ama formation and metabolic imbalance, corresponding to disrupted metabolic functions described in modern physiology. Discussion: Agni plays a crucial role in transforming food components of various origins into a homologous nature, to turn digested food into energy. According to the functions and site of action, Agni has been divided into 13 types, i.e., one Jatharagni, five Bhutagni, and seven Dhatvagni. Jatharagni is the most important one, which digests four types of food and transforms them into Rasa and Mala. The discernment of Agni ultimately determines which materials enter our cells and tissues and which should be eliminated as waste. Hence, understanding of Agni is one of the important concepts for the understanding of its modern interpretations on metabolism. +Conclusion: Agni is in charge of absorbing nutrient-dense substances; it is essential for converting food into energy and controls internal metabolic processes. The result is the body being nourished, which improves its complexion, nutritional strength, and overall well-being.